Size‐Differentiated Export Flux in Different Dynamical Regimes in the Ocean. Issue 3 (26th March 2021) - Dever, M.; Nicholson, D.; Omand, M. M.; Mahadevan, A.
Abstract: Export of Particulate Organic Carbon (POC) is mainly driven by gravitational sinking. Thus, traditionally, it is thought that larger, faster‐sinking particles make up most of the POC export flux. However, this need not be the case for particles whose sinking speeds are comparable to the vertical velocities of a dynamic flow field that can influence the descent rate of particles. Particles with different settling speeds are released in two process‐oriented model simulations of an upper ocean eddying flow in the Northeast Pacific to evaluate the impact of (1) ocean dynamics on the respective contribution of the different sinking‐velocity classes to POC export, and (2) the particle number size‐spectrum slope. The analysis reveals that the leading export mechanism changes from gravitationally driven to advectively driven as submesoscale dynamics become more active in the region. The vertical velocity associated with submesoscale dynamics enhances the contribution of slower‐sinking particles to POC export flux by a factor ranging from 3 to 10, especially where the relative abundance of small particles is large (i.e., steep particle size‐spectrum slope). Remineralization generally decreases the total amount of biomass exported, but its impact is weaker in dynamical regimes where submesoscale dynamics are present and export is advectively driven. In an advectively driven export regime, remineralization processes counter‐intuitively enhance the role of slower‐sinking particles to the point where these slower‐sinking velocity classes dominate the export, therefore challenging the traditional paradigm for POC export. This study demonstrates that slow‐sinking particles can be a significant contribution, and at times, even dominate the export flux. Key Points: Submesoscale dynamics enhance the contribution of slow‐sinking particles to particulate organic carbon (POC) export, especially for steep particle size‐spectrum slopes Remineralization processes intensify the role of slow‐sinking particles, to the point where these particle sometime dominate POC export